Cara Guru Menciptakan Lingkungan Belajar yang Aman, Nyaman, Menyenangkan di Dalam Kelas bagi Siswa Sekolah Dasar - Mendrofa, Cheline Nismeta Rotua; Kuntarto, Eko; Pamela, Issaura Sherly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
A safe, comfortable, and enjoyable learning environment is an essential requirement for the achievement of effective learning. Teachers play a role not only as transmitters of knowledge but also as managers of the classroom atmosphere who are able to facilitate students cognitive, social and emotional development. This study aims to describe how teachers create a conducive learning environment in elementary schools, the challenges they face, and the supporting factors that influence their success. This research employed a qualitative approach with a phenomenological method. The subject of the study was a sixth-grade teacher at SD Negeri 138/IV Kota Jambi. Data were collected through interviews, observations, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. To ensure data validity, technique triangulation was applied. The findings reveal that teachers encounter various challenges, including physical constraints (limited classroom space, lack of facilities, power outages), social constraints (differences in student characteristics, peer conflicts), and psychological constraints (students low self-confidence, emotional pressure, and teacher burnout). Nevertheless, teachers implement strategies to overcome these obstacles, such as arraging the classroom more flexibly, fostering positive social interactions, creating a psychologically safe atmosphere, and demonstrating a friendly and open personality. Other supporting factors include the support of the principal, collaboration among teachers, parental involvement, and the utilization of available facilities, infrastructure, and simple technology. This study emphasizes that the creations of a safe, comfortable, and enjoyable learning environment is the result of synergy among teachers, schools, parents, and the surrounding environment. Thus, teachers cannot work alone but require comprehensive systemic support.